Dobro wspólne jako kategoria normatywna - Młynarska-Sobaczewska, Anna (Acta Universitatis Lodziensis. Folia Iuridica, 2009)
The term “common good”, understood as the good shared by all the society (community), is well known in ancient and modern philosophy and in theory of politics, but very seldom is directly articled in law documents. This idea of common good has few senses described in the article: aggregative, common, suppressive, and integral. Always, however, the idea has been connected with doctrine of natural law. The term “common good” has also normative sense. This article compares the senses of Irish and Polish Constitutions, both of them use this idea in normative texts. Analysis of Polish Constitutional Tribunal decisions leads to conclusion that the sense of common good in Polish practice is not clear and has very weak association with doctrine (of natural law).